The Effect of Unemployment and Low-Quality Work Conditions on Work Values: Exploring the Experiences of Young Europeans. Issue 1 (March 2019) - Rainsford, Emily; Maloney, William A.; Popa, Sebastian Adrian
This article examines the impact that unemployment and low-quality work conditions have on young adults' work values. Academic theory suggests that harsher economic conditions will make people prize extrinsic work values (income, security) more and intrinsic work values (creative, independent working conditions, autonomy) less. We apply this reasoning to study young Europeans' response to unemployment and low-quality work conditions, expecting that those who have these experiences will value extrinsic values more and intrinsic work values less than those who do not have these experiences. Using the CUPESSE dataset of 18- to 35-year-olds in eleven European countries, we do not find support for the effect of previous unemployment experience on intrinsic or extrinsic work values. However, when it comes to the effect of low-quality work conditions, there are mixed results. We find that one dimension of low-quality work conditions—overqualification—does have a positive effect on extrinsic work values. Further, we find that age has a moderating effect: unemployment and low-quality work conditions have a larger impact on the younger workers in our sample than their older counterparts.